PHYTOCHEMICAL SCREENING AND HPTLC FINGERPRINTING ANALYSIS OF ETHANOLIC EXTRACT OF ERYTHRINA VARIEGATA L. FLOWERS - Hemmalakshmi, Subrhamanian; Priyanga, Suriyamoorthy; Devaki, Kanakasabapathi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Medicinal plants possess phytochemicals that accumulate in various parts of plant like leaves, flowers, vegetables and roots that exert defense mechanism and protect us from various diseases. The present study was carried out to investigate the secondary metabolites and develop HPTLC fingerprinting of Erythrina variegata L. Methods: The Phytochemical screening was analyzed for various extracts by using standard protocols and HPTLC analysis was carried out for the identification of alkaloids, flavonoids, glycosides, saponin and steroids in the ethanolic extract of Erythrina variegata L. flower. Results: The phytochemicals screening confirms the presence of phyto-constituents in various plant extracts of Erythrina variegata L. The study revealed the presence of alkaloids, flavonoids, glycosides, saponin and steroids in the ethanolic extract of Erythrina variegata L. flower. Conclusion: Based on the study it is concluded that Erythrina variegata L. flower possess phytochemicals like alkaloids, flavonoids, glycosides, saponin and steroids. Keywords: Erythrina variegata L., HPTLC, Medicinal plants, Phytoconstituents, Secondary metabolites